Edaravone (MCI-186) is effective as a free radical scavenger following arteriovenous sheathotomy for treatment of macular oedema associated with branch retinal vein occlusion. Issue 11 (9th August 2009) - Maeno, T; Tano, R; Takenaka, H; Mano, T
Abstract : Aims: To determine whether edaravone (MCI-186), a free radical scavenger, can reduce macular oedema and improve the visual acuity after arteriovenous sheathotomy in eyes with a branch retinal vein occlusion (BRVO). Methods: Forty-seven eyes of 47 consecutive patients with a BRVO who were treated with arteriovenous sheathotomy were studied. The patients were assigned prospectively to either Group R who received 30 mg of edaravone (Radicut) systemically during the vitrectomy or Group N who did not receive any drugs. The postoperative visual acuity was measured before and 12 months after the operation. Results: At 12 months postoperatively, the best-corrected visual acuity (BCVA) in logarithm of the minimum angle of resolution (logMAR) units improved significantly from 0.22 to 0.56 logMAR units in Group R and from 0.20 to 0.27 units in Group N (p = 0.016). Twenty-three of 27 cases (85%) in Group R and four of 15 cases (27%) in Group N showed an improvement in BCVA of >0.2 logMAR units (p = 0.0025). Conclusion: The better visual acuity in patients given edaravone than those without endaravone during the arteriovenous sheathotomy suggests that edaravone improved the physiology of the retinal cells after the arteriovenous sheathotomy.